Validation of an analytical method to quantify serum electrolytes by atomic absorption spectroscopy - García-Alegría, Alejandro Monserrat; Gómez-Álvarez, Agustín; García-Rico, Leticia; Serna-Félix, Mercedes (Acta Universitaria, 2015)
The objective of this research was to develop the procedure to validate an analytical method through the technique of spectroscopy by atomic absorption to quantify serum electrolytes. Quality parameters were used such as: accuracy, precision, repeatability, linearity, limit of detection, and limit of quantification. First some work was done in optimization of the analytical method in ideal conditions. Subsequently, some work was done with the validation of the method using a certified reference material National Institute Standard Technology (NIST) 2670a. Finally, the methodology was assessed in the determination of metals in a sample of human blood serum. The quality criteria evaluated showed consistent and acceptable values depending on the statistical test used for each parameter with a significance level of 5% (α = 0.05). The results obtained in this research can contribute to the beginning of the establishment of an official standard aimed at analysis of electrolytes (Na, K, Ca, Mg) in human blood serum so that can be used as reference by clinical laboratories, public health institutions, as well as in institutions of higher education and research centers.